THE EFFECT OF COMPETITIVE ADVANTAGE AND SUSTAINABLE MANAGEMENT ON SUSTAINABILITY PERFORMANCE - Putu Ayu Sita Laksmi; Komang Adi Kurniawan Saputra; Noorliza MD. Noordin; Carlos Afonso Bareto (Jurnal Bisnis dan Akuntansi, 2024)
This research aims to examine and analyze the role of the influence of competitive advantage and sustainable management on sustainability performance in hotels based on the provisions of the Global Sustainable Tourism Council (GSTC). The research approach uses survey-based quantitative research methods in all four and five star hotels in Indonesia, totaling 1,010 hotels. Data was collected using a questionnaire using digital tools, namely Google Form. The collected data was analyzed using a multiple linear regression mechanism. Empirical research findings show that competitive advantage and sustainable management have a significant positive effect on improving hotel sustainability performance. The originality of the research is demonstrated by the use of sustainability performance indicators based on the Global Sustainable Tourism Council which is still guided by the triple bottom line principle, but there are cultural sustainability principles that are in accordance with Indonesia's tourism orientation.